Isolation and characterization of necrosis-inducing phytophthora protein 1 (npp1) gene from plants pathogen Phytophthora cinnamomi - Martins, Ivone (2014)
Oomycetes from the genus Phytophthora are fungus-like plant pathogens that are devastating for agriculture and natural ecosystems. Due to their particular physiological characteristics, no efficient treatments against diseases caused by these microorganisms are presently available. To develop such treatments, it appears essential to dissect the molecular mechanisms that determine the interaction between Phytophthora species and host plants. One of the most widely distributed Phytophthora specie, with nearly 1000 host species is Phytophthora cinnamomi. Associated with this pathogen is the ink disease of Castanea Sativa Mill being one of the most destructive diseases in C. Sativa in the northeast of Portugal and the most common symptoms are root necrosis and reduction in root growth, which invariably lead to the trees death. P. cinnamomi is able to secrete a novel class of necrosis-inducing proteins, known as Nep1-like proteins (NLPs), more specifically necrosis-inducing Phytophthora protein 1 (npp1), that causes necrosis on leaf and roots of the plant, leading to the plant death. In order to better evaluate the mechanism of plant necrosis induced by P. cinnamomi. The study of factors that affect npp1 gene expression is extremely important. The npp1 gene ORF comprises 770 bp encoding a 256 aa protein with a molecular weight of approximately 25 kD. In order to understand its function, gene expression in vitro in P. pastoris (heterologous expression), was studied during growth in different carbon sources, by RT-qPCR. Over expression of our gene in P. pastoris was also performed. In vivo expression technology has been used to study the expression of npp1 gene from fungi during infection by RT-PCR. In our work chestnut roots were infected with P. cinnamomi and mRNA was extracted at different times of infection to analyze gene expression. These and other results will be presented and discussed.